Improvement Production of Hyaluronic Acid by Streptococcus zooepidemicus in Sugarcane Molasses - Pan, Nicole Caldas (2017)
Microbial hyaluronic acid (HA) production has been preferred rather than extraction from animal tissue for medical and cosmetic applications. In this context, to obtain an economically competitive HA production by Streptococcus zooepidemicus, culture conditions were studied to improve the polymer production in sugarcane molasses. The highest HA production by S. zooepidemicus ATCC 39920 achieved was 2.825 g. L−1 in a 4.5 L bioreactor with controlled pH (8.0) and medium containing molasses (85.35 g.L−1 total sugar) pretreated with activated charcoal and yeast extract (50 g.L−1). The HA produced exhibited a high molecular weight of 1.35 × 103 kDa and the DPPH radical scavenging activity of the polymer at 1 g.L−1 was 41 %. The FTIR and UV-Vis spectra showed no substantial differences in the spectral pattern between produced and standard HA. This study is a promising strategy for sugarcane molasses application by producing high value-added products such as hyaluronic acid.